Pillars of Computer Science: essays dedicated to Boris (Boaz) Trakhtenbrot on the occasion of his 85th birthday - Avron, Arnon (Springer, 2017)
"This festschrift is dedicated to Boris Trakhtenbrot on the occasion of his 85th birthday. … The volume covers a wide variety of papers on logic and the foundations of theoretical computer science, written by top people in the field. It is certainly worth acquiring for a library." (K. Lodaya, ACM Computing Reviews, January, 2009)